LEARNING ARABIC QAWĀ‘ID THROUGH INSTAGRAM: A MULTIMEDIA LEARNING PERSPECTIVE - Fayza Maulidia; Maman Abdurahman (Universitas Islam Sumatera Utara (UISU), 2026)
This study investigated the use of the Instagram account @arabfaham as a medium for learning Arabic grammar (qawā‘id) from the perspective of the Cognitive Theory of Multimedia Learning. It aimed to examine how multimedia-based content can address learners’ difficulties in understanding qawā‘id, which are often perceived as abstract and theoretical. A descriptive qualitative method was used to analyze the presentation of instructional content and user responses. Data were collected through documentation of selected Instagram Reels focusing on mubtada’ and khabar, as well as online interviews with users. The findings showed that the content was mainly delivered through interactive quizzes combining Arabic text and visual elements, which supported active cognitive processing. User interactions indicated a high level of engagement, particularly through answering questions and participating in discussions in the comment section. Furthermore, the content reflected key principles of multimedia learning, including dual channel, limited capacity, active processing, contiguity, segmenting, and personalization. These studies contributed to the growing body of research on digital language learning by demonstrating that Instagram can serve not only as a content delivery platform but also as an interactive learning environment that enhances learners' understanding and practical application of Arabic grammatical structures.